Dynamic capabilities in Italian leading SMEs adopting industry 4.0 - Garbellano, S.; Da Veiga, M. R. (Measuring Business Excellence, 2019)
Purpose This paper focuses on how Industry 4.0 technology transfer has been implemented by leading Italian innovative small and medium-sized companies (SMEs). Design/methodology/approach This exploratory-descriptive study uses qualitative methods for collecting primary data (interviews and ethnographic observation) and secondary data (surveys, press news, and websites). Findings The paper contributes to the understanding of what building Dynamic Capabilities DC is and to clarify pivotal roles, functions, and dynamics of the entrepreneur and the executive team. Research Limitations/Implications The results that emerged from the present research unveil a great potential for further development. The study can be confirmed and/or extended by replicating it within other economic contexts such as the European Union allowing then comparative studies amongst regions and countries. Practical Implications In Italian leading SMEs an "augmented management" emerged. The study shows that digital technologies are enriching not only “what” and “how” management performs its duties, but also its role: “orchestration” – a key term in DC theory – has been enhanced by new meanings. Originality/value Implementing Industry 4.0 has required a renewal of the leading executive team: new young executives coming from other companies and sons/daughters of the entrepreneurs have provided methodologies and commitment to foster the digital transformation. Social implication The study points out the relevance of an inclusive approach to Industry 4.0 to leverage the collective intelligence of the company.